Multimedia Interaktif Berbasis Edpuzzle: Upaya Meningkatkan Keterampilan Berpikir Kritis Siswa dalam Pembelajaran Biologi - Sinaga, Sabilah Allyu; Adlini, Miza Nina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop interactive multimedia based on the Edpuzzle application that is valid, practical, and effective to improve students’ critical thinking skills. The method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study were 36 students of grade XI Madrasah Aliyah Laboratorium UINSU. Data were collected through validation questionnaires from media and material experts, questionnaires on the practicality of teachers and students, and a critical thinking skills test using the Facione indicator. The results of the validity test showed that interactive multimedia was in the very valid category with a score of 96.25% from material experts and 97.5% from media experts. Based on the practicality test, it obtained a score of 100% from teachers and 91% from students, including the very practical category. The results of the effectiveness test showed an increase in students’ critical thinking skills with a very effective category with a score of 75%. These findings prove that Edpuzzle-based interactive multimedia can be an alternative learning media that is relevant to the demands of the 21st century and is able to facilitate student engagement and strengthen critical thinking skills in a structured manner.